Groundwater dynamics in subterranean estuaries of coastal unconfined aquifers: Controls on submarine groundwater discharge and chemical inputs to the ocean. (May 2018) - Robinson, Clare E.; Xin, Pei; Santos, Isaac R.; Charette, Matthew A.; Li, Ling; Barry, D.A.
Highlights: Driving forces on flow and transport, and chemical behavior in subterranean estuaries reviewed. Need for better understanding of interactions between physical and biogeochemical processes. Need to consider influence of real work complexities such aquifer heterogeneities. Abstract: Sustainable coastal resource management requires sound understanding of interactions between coastal unconfined aquifers and the ocean as these interactions influence the flux of chemicals to the coastal ocean and the availability of fresh groundwater resources. The importance of submarine groundwater discharge in delivering chemical fluxes to the coastal ocean and the critical role of the subterranean estuary (STE) in regulating these fluxes is well recognized. STEs are complex and dynamic systems exposed to various physical, hydrological, geological, and chemical conditions that act on disparate spatial and temporal scales. This paper provides a review of the effect of factors that influence flow and salt transport in STEs, evaluates current understanding on the interactions between these influences, and synthesizes understanding of drivers of nutrient, carbon, greenhouse gas, metal and organic contaminant fluxes to the ocean. Based on this review, key research needs are identified. While the effects of density and tides are well understood, episodic and longer-period forces as well as the interactions between multiple influences remain poorly understood. Many studies continue to focus on idealized nearshore aquifer systems and future work needs to consider real world complexities such as geological heterogeneities, and non-uniform and evolving alongshore and cross-shore morphology. There is also a significant need for multidisciplinary research to unravel the interactions between physical and biogeochemical processes in STEs, as most existing studies treat these processes in isolation. Better understanding of this complex and dynamic system can improve sustainable management of coastal water resources under the influence of anthropogenic pressures and climate change.